Research on The Production and Application of Multifunctional Concrete - Gong, Peiqi (Transactions on Engineering and Technology Research, 2024)
As the preparation of building materials can pollute the environment, and the manufacturing process is complicated and wastes materials, people are developing more advanced multi-functional concrete. This paper studies the development and application of two new types of concrete, as well as some of their shortcomings and development process. Firstly, electricity-based multifunctional concrete not only has the advantages of traditional concrete, but also has strong electrical conductivity, thermoelectricity and capacitance. This kind of concrete holds significant promise in a variety of engineering applications, such as structural health monitoring, traffic detection, and snowmelt. It not only makes people's life more convenient, but also ensures that the concrete preparation process can reduce the damage to the environment. Secondly, this paper analyzes a new type of concrete. The concrete can be made from seawater and carbon dioxide, which can reduce carbon emissions and be used to make wave-absorbing blocks. However, as this new concrete is newly developed, it is somewhat lacking in some aspects, such as it is not as strongly alkaline as ordinary concrete. Conclusion shows that the development of new multifunctional concrete can reduce the pollution to the environment and meet the needs of modern society for concrete, which has important practical significance.